The Feasibility of Learning Macromedia Flash 8 Multiple Intelligences Class IV Elementary School - Masruriyah, Jois Syahadati; Istiningsih, Galih (Prosiding University Research Colloquium, 2022)
This research is motivated by the lack of students' mathematical communication in learning mathematics, especially in the length material unit. In addition, this research was conducted to determine the feasibility of a learning media, namely "macromedia flash MI", this media is considered to provide convenience for students in understanding the material. This study aims to determine the feasibility of macromedia flash MI media in the length material unit for fourth grade mathematics at SDN Danupayan. This study uses research and development methods (Research and Development). The time for the research to be carried out is in the odd semester of the 2021/2022 academic year with the research subjects are grade IV students SDN Danupayan. The media validation shows a percentage of 97.2% which can be concluded that the media validity shows the Very Valid (SV) category with an interval between the percentages of 81.25%–100%. The data was obtained from 3 validators, they are 1 lecturer at the University of Muhammadiyah Magelang and 2 teachers at SDN Danupayan. Then the results of the research on student responses to the media showed a percentage of 82.16% which can be concluded that the validity of the media showed the Very Valid (SV) category with an interval between the percentages of 81.25-100%. The data was obtained from the questionnaire data of 6 respondents. Thus, MI macromedia flash media is suitable for use in learning.